PEMIDANAAN DAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI DI INDONESIA SEBAGAI UPAYA PEMULIHAN KERUGIAN KEUANGAN NEGARA - Liantha Adam Nasution; Roni Risky Nasution (CV. Denasya Smart Publisher, 2025)
Additional penalties in the form of monetary compensation in Indonesia’s corruption punishment system serve as instruments for recovering state financial losses and as a means of deterrence. This article analyzes the normative framework for the punishment of corruption crimes, focusing on the concept and mechanism of monetary compensation based on Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 and its application in court decisions. The novelty of this research lies in the integration of normative analysis with jurisprudential review of the practice of imposing and executing monetary compensation, so that it not only assesses the appropriateness of legal regulations but also the effectiveness of their implementation in criminal courts. This research uses a normative legal method with a legislative and jurisprudential approach through a literature study of primary and secondary legal materials. The results of the study show that although the regulation of monetary compensation has a clear legal basis, its implementation still faces obstacles in the form of inconsistencies in sentencing, difficulties in asset tracing, and obstacles in the execution of decisions, which have resulted in the recovery of state financial losses not being optimal. Therefore, this study recommends harmonizing regulations, strengthening technical guidelines for the judiciary, and increasing the capacity of law enforcement officials in order to achieve effective and fair punishment for corruption.